Storyboarding for visual analytics. (January 2015) - Walker, Rick; ap Cenydd, Llyr; Pop, Serban; Miles, Helen C; Hughes, Chris J; Teahan, William J; Roberts, Jonathan C
Analysts wish to explore different hypotheses, organize their thoughts into visual narratives and present their findings. Some developers have used algorithms to ascertain key events from their data, while others have visualized different states of their exploration and utilized free-form canvases to enable the users to develop their thoughts. What is required is a visual layout strategy that summarizes specific events and allows users to layout the story in a structured way. We propose the use of the concept of 'storyboarding' for visual analytics. In film production, storyboarding techniques enable film directors and those working on the film to pre-visualize the shots and evaluate potential problems. We present six principles of storyboarding for visual analytics: composition, viewpoints, transition, annotability, interactivity and separability. We use these principles to develop epSpread, which we apply to VAST Challenge 2011 microblogging data set and to Twitter data from the 2012 Olympic Games. We present technical challenges and design decisions for developing the epSpread storyboarding visual analytics tool that demonstrate the effectiveness of our design and discuss lessons learnt with the storyboarding method.